Online Learning Challenges and Coping Among U.S. College Students During COVID-19 Lockdown and Two Years After - Alhazani, Hayaa; Chen, Li-Ting (Journal of educational technology development and exchange, 2025)
There is a lack of research on comparing college students’ learning experiences during and after the COVID-19 lockdown. Moreover, little is known about the relationship between student coping and perceived online learning challenges in higher education. The present study aimed to fill in the gap. Online survey responses from 43 U.S. college students were used in this correlational study. Learning environment challenges were rated as the greatest challenges during the lockdown and two years after it. Students who had taken online classes before the lockdown rated higher levels of technological complexity during the lockdown than their counterparts. When comparing coping strategies, findings revealed that planning was used more frequently during the lockdown than two years after it. Based on the coping circumplex model (Stanisławski, 2019), students were divided into four groups: problem-solving coping, preoccupation with the problem coping, hedonic disengagement coping, and problem avoidance coping. Students who engaged in a problem-solving coping style rated lower levels of various online learning challenges during the lockdown than their peers who engaged in other coping styles. Based on the findings, an orientation that introduces strategies for establishing a productive online learning environment and active coping with online learning difficulties is recommended for online instructors. The findings not only shed light on online instruction but also have implications for coping research.